PRESERVASI SENYAWA FENOLIK DAN ANTIOKSIDAN PADA PROSES SANGRAI BIJI KAKAO DENGAN MENGGUNAKAN VACUUM DRYING OVEN - Dhanang Puspita, Monang Sihombing dan Mayer Tinting Sirenden (Department of Agroindustrial Technology, Bogor Agricultural University, 2018)
Indonesia is the biggest cacao producer in Asia and third biggest in the world, however, Indonesian cacao has low quality due to partial fermentation. Late 2010 almost all of the cacao production is exported in dried beans with a lower price than world’s cacao price rate. Export tax of cacao beans policy was changed to 15% in 2011 which conduce replacement of cacao beans export to finished product export. Innovation in cacao beans processing is important to develop escepially for agroindustry field. Cacao beans roasting process is important thing in chocolate processing. During the roasting process, phenolic compounds and methylxanthine of cacao beans were denatured. Vacuum drying oven is one of the alternative process which can preserve bioactive compounds. Thus, the aim of this research is to give information about effect of vacuum drying oven in total phenolic and antioxidant activity. Analysis methods used were total phenolic and antioxidant activity (IC-50) analysis. The result shown that vacuum drying oven has significant effect on total phenolic and antioxidant activity with three times higher in concentration than conventional method. The highest antioxidant activity and total phenolic content at 80°C and 75 minutes. Therefore, vacuum drying oven can be used as an alternative method with an advantage like preserve bioactive compound in cacao beans.Keywords: antioxidant, cacao, phenolic, roasting, vacuum drying